Integrity and Transparency in Public Procurement as a Tool for Effectiveness and Efficiency in pos-COVID Public Management - Campos Acuña, Concepción (Revista del CLAD Reforma y Democracia, 2022)
This work addresses the new realities of public procurement in the scenario marked by the COVID-19 pandemic, where the instrumental nature of public procurement to provide citizens with quality public goods and services takes the spotlight. Procurement is presented as one of the driving forces for the implementation of recovery and transformation projects in the countries, through different public policies and programs such as the EU Next Generation Funds. Therefore, as analyzed in this document, it will be necessary to maximize integrity and transparency in the different procurement procedures in pursuit of greater effectiveness and efficiency in public management aligned with the Sustainable Development Goals and the 2030 Agenda. According to OECD, procurement is the area of greatest risk of public corruption. To approach the challenges posed, the paper is articulated around a series of proposals to characterize the efficiency model that is so necessary in procurement, given its instrumental nature in achieving the objectives of public policies. The dimension of digital transformation and digitization of procurement processes is analyzed, with the projection offered by the publication of training, in terms of social control and openness of procurement, through electronic channels and the possibilities arising in terms of analysis and massive data processing for effective accountability. It also takes into consideration the implementation of compliance techniques, such as post-pandemic integrity systems, which allow an integral management of ethics in public procurement, the reinforcement of institutional capacities in procurement, and the professionalization of public servants to ensure an effective rationalization of public expenditure and continuous improvement in the quality of public management. The analysis is completed with a proposal for the revision of integrity indicators, focusing on the phases before and after the bidding procedure, planning and execution as basic premises of the new model. The recovery model articulated in Europe, through the Recovery Mechanism with the Next Generation EU Funds, and the need to coordinate risk prevention and management mechanisms in its contracting, are exposes. In short, the study shows how the management of post-COVID public procurement should be more effective and efficient, avoiding the lack of transparency leading to market capture and inefficiencies due to lack of integrity. To this end, in a critical context such as the current one, transparent and integral procurement is presented as a key tool.
Keywords: Contract Policy; Public Contracts; Crisis Management; Efficacy; Efficiency; Transparency; Ethics